2021
DOI: 10.1038/s41598-021-95731-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle shape on the deformation and stress reduction of a gravel soil due to wetting

Abstract: This paper investigates the effect of particle shape on the stress reduction and collapse deformation of gravelly soil using a medium-scale direct shear test apparatus under different relative densities, normal stress, and shear stress levels. A new method based on the Micro-Deval test was introduced to produce sub-angular particles from angular particles. Therefore, two series of soil specimens were obtained with the same rock origin, particle size distribution, and relative density but different particle sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As the key component of soil texture, the content and distribution of gravel particles affect soil physical structure and hydrological processes such as soil water storage, runoff, water infiltration, solute transport, and water flow (Dan et al, 2023; Mahinroosta & Oshtaghi, 2021; Qiu et al, 2015; Smets et al, 2011; Wang et al, 2019); they also could reduce the mechanical resistance to root extension (Alameda & Villar, 2012), and may cause root aggregation and growth (Clark et al, 2003). Howover, the impact and the underlying mechanism of soil gravels are relatively complex (Han et al, 2021; Li, Wang, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As the key component of soil texture, the content and distribution of gravel particles affect soil physical structure and hydrological processes such as soil water storage, runoff, water infiltration, solute transport, and water flow (Dan et al, 2023; Mahinroosta & Oshtaghi, 2021; Qiu et al, 2015; Smets et al, 2011; Wang et al, 2019); they also could reduce the mechanical resistance to root extension (Alameda & Villar, 2012), and may cause root aggregation and growth (Clark et al, 2003). Howover, the impact and the underlying mechanism of soil gravels are relatively complex (Han et al, 2021; Li, Wang, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…shear strength, peak friction angle, etc) of sandy soils. With the support of a medium-scale direct shear device, Reza Mahinroosta et al [2] investigated the influence of particle morphology on stress reduction and collapse deformation in gravelly soils under varying relative densities, normal stresses, and shear stresses. In addition, Yang Lin et al [3] observed obvious structural failure and rearrangement of a two-dimensional stacked lattice granular system when being compressed.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of particles has a significant effect on interactions with fluids 7 . In the field of macro- and microgeotechnical mechanics, the shape of particles can affect the mechanical properties of sand 8 , 9 . Researchers have conducted the discrete element method (DEM) simulations to study the macroscopic and microscopic mechanical behavior of sand particles 10 15 , based on the true shape of the particles and the generation of angular particles 16 18 .…”
Section: Introductionmentioning
confidence: 99%